2014
DOI: 10.5194/acp-14-5547-2014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mixed layer heights from airborne high spectral resolution lidar, ground-based measurements, and the WRF-Chem model during CalNex and CARES

Abstract: Abstract. The California Research at the Nexus of Air Quality and Climate Change (CalNex) and Carbonaceous Aerosol and Radiative Effects Study (CARES) field campaigns during May and June 2010 provided a data set appropriate for studying the structure of the atmospheric boundary layer (BL). The NASA Langley Research Center (LaRC) airborne high spectral resolution lidar (HSRL) was deployed to California onboard the NASA LaRC B-200 aircraft to aid in characterizing aerosol properties during these two field campai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(112 citation statements)
references
References 35 publications
(42 reference statements)
3
109
0
Order By: Relevance
“…As with previous studies (Brooks, 2003;Baars et al, 2008;Compton et al, 2013;Scarino et al, 2014), the dilation factor a affects the number of covariance wavelet transform coefficient (CWTC) local minimums. Larger values create a few large local minimums (Fig.…”
Section: Haar Wavelet Methodsmentioning
confidence: 88%
See 2 more Smart Citations
“…As with previous studies (Brooks, 2003;Baars et al, 2008;Compton et al, 2013;Scarino et al, 2014), the dilation factor a affects the number of covariance wavelet transform coefficient (CWTC) local minimums. Larger values create a few large local minimums (Fig.…”
Section: Haar Wavelet Methodsmentioning
confidence: 88%
“…Out of the three methods tested in this study, it is suggested to employ the wavelet method in future studies, in particular for longterm seasonal and diurnal boundary layer studies and spatial analysis of the BL using multiple lidar aerosol backscatter measurements. A combination of the wavelet method BLH retrievals during clear skies and the cluster analysis method's ability to calculate cloud depth is also recommended for more robust BL studies to retrieve more information about the boundary layer under both conditions, as both the wavelet and cluster analysis methods were seen to perform well using various lidar instruments in studies such as Compton et al (2013), Scarino et al (2014), and Toledo et al (2014). Although not tested in this study, recent work by de Bruine et al (2016) and Poltera et al (2017) show promising results using an automated method which reduces incorrect detection of the BLH using graph theory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Model configuration-2 (WRF-2) is a sensitivity test for which we replaced the boundary layer configuration used in WRF-1 with Mellor-Yamada-Nakanishi-Niino (MYNN; Nakanishi and Niino, 2009). Previous studies evaluating WRF performance in Southern California have identified PBL schemes as a primary source of error (Huang et al, 2013;Scarino et al, 2014). These studies established that available parameterization schemes produce significant differences in PBL height compared to large-eddy simulated (Huang et al, 2013) and light detection and ranging (LIDAR) estimates (Scarino et al, 2014), and that these issues are exacerbated near the coastal zone, which adversely affects the simulation of sundowner wind influence over SB (communication with NWS LA/Oxnard office).…”
Section: Methodology: Model Configurationmentioning
confidence: 99%
“…Previous studies evaluating WRF performance in Southern California have identified PBL schemes as a primary source of error (Huang et al, 2013;Scarino et al, 2014). These studies established that available parameterization schemes produce significant differences in PBL height compared to large-eddy simulated (Huang et al, 2013) and light detection and ranging (LIDAR) estimates (Scarino et al, 2014), and that these issues are exacerbated near the coastal zone, which adversely affects the simulation of sundowner wind influence over SB (communication with NWS LA/Oxnard office). The MYNN PBL parameterization was adopted in WRF-2 because of the reported improvement of the turbulent length scale that realistically increases with decreasing stability, and the improvement of the expression for stability functions for momentum and heat.…”
Section: Methodology: Model Configurationmentioning
confidence: 99%